Komentarz jako gatunek w telewizyjnych programach informacyjnych - Wardzała, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
One of the new elements of a news programme, evolved as a result of the changes in the its formal structure, is the commentary, which introduces some variety to the poetics of the news story as well as makes the actual presentation more attractive. The issue has not been, however, adequately addressed and discussed in the literature of the subject and there are only selective characteristics of some of its varieties available. The present article provides a description of different types of the informative commentary and its particular place within the structure of a programme for this genre is dependable on the information it refers to and on the involved relation between the two (how it is organized by and organizes). Additionally, the article discusses the form of the commentary and conceivable perceptional planes in which it can be manifested.